Does post‐anthesis heat stress affect plant phenology, physiology, grain yield and protein content of durum wheat in a semi‐arid Mediterranean environment?. (21st December 2018) - Cosentino, Salvatore L.; Sanzone, Emanuele; Testa, Giorgio; Patanè, Cristina; Anastasi, Umberto; Scordia, Danilo
Abstract: Increasing air temperature due to changing climate is projected to decrease the length of the growing season, hasten vegetative development and maturation, and ultimately affect yield of many C3 crops. Previous multilocation trials highlighted strong relationships between thermal trends in the interval "beginning of flowering‐end of grain filling" and grain yield, and protein content in durum wheat ( Triticum turgidum subsp. durum (Desf.) Husn.). With the aim to confirm these relationships, nine durum wheat genotypes, including old (Capeiti 8, Senatore Cappelli and Trinakria) and modern (Amedeo, Arcangelo, Mongibello, Simeto, and Svevo) varieties and a Sicilian landrace (Russello) were grown at three different sites representing a climate gradient in Sicily, Italy. Moreover, the effect of post‐anthesis heat stress on these durum wheats was further investigated in two contrasting environments: open‐field (control—C) and greenhouse heat stress (HS). HS shortened the interval "beginning‐end of flowering" of 1.5 days across genotypes, and the "end of flowering‐beginning of grain filling" and maturation of 4.9 days, with a range of 1 day in Arcangelo to 11 days in Cappelli. Advances in main phenophases significantly decreased kernel weight (KW) and grain yield (GY), whereas grain protein content (PC) increased. As expected, a negative relationship was observed between GY and PC, while positive relationships were found for GY and grain‐filling duration (GFD), and GY and KW. Genotypes responded differently to heat stress, as evidenced by the net photosynthesis, transpiration rate, instantaneous water use efficiency and dry matter accumulation in kernels. Genotypes were ranked according to the heat susceptibility index (HSI): Amedeo, Arcangelo, Capeiti 8, Svevo and Trinakria resulted heat‐tolerant. These varieties were characterized by an early trigger of dry matter accumulation in kernels under HS (Amedeo, Arcangelo and Trinakria), or showed similar length of the GFD (Capeiti 8) between environments. The multilocation trial confirmed a negative relationship between maximum temperatures and grain yield, and a positive relationship between minimum temperatures and protein content during grain–filling periods. Research focusing on agronomic strategies, phenology and breeding for tolerance to heat stress is of strategic importance to cope with the detrimental effect of global warming in semi‐arid climates.